Nemotelus flavipes De Geer, 1776 recognized as a nomen oblitum and synonym of Pandivirilia eximia (Meigen, 1820) (Diptera: Therevidae) - Holston, Kevin C. (Zootaxa, 2004)
An overlooked De Geer name, Nemotelus flavipes De Geer, 1776 has been identified as synonymous with Pandivirilia eximia (Meigen, 1820), a name in use for a species of stiletto fly (Diptera: Therevidae). The type specimen has been lost, and this synonymy is based on the original description and associated figures provided by De Geer. Nemotelus flavipes De Geer, 1776, is a nomen oblitum and Thereva eximia Meigen, 1820 is a herein recognized as a nomen protectum in accordance with Article 23.9.2 of the International Code of Zoological Nomenclature, which maintains prevailing name usage for the species Pandivirilia eximia (Meigen, 1820).